PENINGKATAN PRODUKSI PETANI LAHAN KERING MELALUI BUDIDAYA SEMANGKA BERBASIS TEKNOLOGI IRIGASI UNTUK MENCETAK PETANI MUDA MILENIAL DAN MEWUJUDKAN PERTANIAN BERKELANJUTAN - Mardi Mardi; Muhammad Fauzi Zulkarnaen; Ahmad Tantoni (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service program was conducted in Sambelia Village, East Lombok Regency, an area characterized by dryland agriculture and high dependency on rainfall. The main problems faced by farmers are limited water resources, low crop diversification, and declining youth interest in the agricultural sector. The program aimed to enhance farmers’ capacity and productivity through the implementation of water-efficient irrigation technology and watermelon cultivation after corn harvest. The activities were carried out in five stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability. Training sessions adopted a learning by doing approach covering dryland watermelon cultivation, drip irrigation systems, organic fertilizer management, and digital marketing. The results indicated a significant improvement in participants’ knowledge and skills, with post-test scores increasing by an average of 47.3% compared to pre-test. In terms of productivity, farmers who previously cultivated corn only once a year were able to add a second cropping cycle with watermelon, resulting in a 166–200% increase in income. This activity demonstrates that the implementation of community-based irrigation technology effectively improves land-use efficiency, farmer independence, and agricultural sustainability in dryland areas.